Análisis comparativo de la situación actual de la preparación del profesional en telecomunicaciones - Saenz De Viteri Mora, Steffany Jamilly (2009)
Telecommunications represents a fundamental area in a growing country, specifically in countries in development ways as ours, for this reason we have made this exhaustive analysis about the actual situation of the professional formation given to telecommunications graduates, and after this get conclusions for heading the education area in the telecommunications in the future. This document starts with statistics about how many graduates exist from 4 Ecuadorian universities, after this we have the most important section of this investigation which contains specifically the received education in telecommunications analysis seen from several angles and applied to 4 Universities, which give us a global vision about this topic Additional to this we have a little statistic study made by survey to get the perception ( satisfaction level) of graduates concerning the received education. Finally we provide the conclusions we have arrived to based in this investigation